2023
DOI: 10.1021/acs.jpcc.3c03189
|View full text |Cite
|
Sign up to set email alerts
|

Production of Single Crystalline Seeds of Organic Nonlinear Optical Materials via Laser Ablation

Abstract: Production of single crystal seeds of organic nonlinear optical materials (4-dimethylamino-N-methly-4-stilbazolium tosylate, DAST) by laser ablation was demonstrated. Here, laser ablation of DAST crystals in a supersaturated solution was induced with focused laser pulses, which resulted in the generation of crystal seeds that grew independently from the original (mother) crystal. We found that the seed crystals showed single crystallinity with nonlinear optical properties (terahertz wave generation), indicatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…For instance, our group has succeeded in triggering crystal nucleation of various organic/biological materials including proteins and pharmaceutical compounds by the focused femtosecond laser irradiation into supercooled/supersaturated liquids, which can produce well-localized stimuli (e.g., cavitation bubbles and shockwave) to crystal nucleation. We also recently reported that ice crystal nucleation could be induced with a single laser pulse, which enables us to monitor the spatiotemporal dynamics of ice crystallization with micrometers and microseconds resolution . In addition, we also demonstrated in situ observation of subsequent crystal growth dynamics from dislocations, cracks, and fragments of crystals that were induced via femtosecond laser ablation of crystals. Notably, various analytical methods (e.g., X-ray diffraction analysis, terahertz wave measurement) confirmed that the quality of crystals did not deteriorate after femtosecond laser ablation, probably because of its thermal-less processing feature. Considering these fine applications of ultrashort laser ablation to crystallization control, ultrashort laser ablation is expected to be utilized as a spatiotemporal trigger for phase transition.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…For instance, our group has succeeded in triggering crystal nucleation of various organic/biological materials including proteins and pharmaceutical compounds by the focused femtosecond laser irradiation into supercooled/supersaturated liquids, which can produce well-localized stimuli (e.g., cavitation bubbles and shockwave) to crystal nucleation. We also recently reported that ice crystal nucleation could be induced with a single laser pulse, which enables us to monitor the spatiotemporal dynamics of ice crystallization with micrometers and microseconds resolution . In addition, we also demonstrated in situ observation of subsequent crystal growth dynamics from dislocations, cracks, and fragments of crystals that were induced via femtosecond laser ablation of crystals. Notably, various analytical methods (e.g., X-ray diffraction analysis, terahertz wave measurement) confirmed that the quality of crystals did not deteriorate after femtosecond laser ablation, probably because of its thermal-less processing feature. Considering these fine applications of ultrashort laser ablation to crystallization control, ultrashort laser ablation is expected to be utilized as a spatiotemporal trigger for phase transition.…”
mentioning
confidence: 92%
“…Since laser irradiation can provide various external perturbations (e.g., chemical bond cleavage, mechanical torque, local melting/sublimination) to crystals depending on laser parameters such as wavelength and pulse duration, we believe future systematic studies will contribute to further precise selective polymorphic control. We foresee that the combination of the laser-induced polymorphic phase transition technique with laser-induced nucleation and growth techniques can expand the horizon of the spatiotemporal control of various crystallization phenomena.…”
mentioning
confidence: 99%